Deficiency of ATP-Binding Cassette Transporters A1 and G1 in Endothelial Cells Accelerates Atherosclerosis in Mice. Issue 7 (July 2016) - Westerterp, Marit; Tsuchiya, Kyoichiro; Tattersall, Ian W.; Fotakis, Panagiotis; Bochem, Andrea E.; Molusky, Matthew M.; Ntonga, Vusisizwe; Abramowicz, Sandra; Parks, John S.; Welch, Carrie L.; Kitajewski, Jan; Accili, Domenico; et al.
Abstract : Objective—: Plasma high-density lipoproteins have several putative antiatherogenic effects, including preservation of endothelial functions. This is thought to be mediated, in part, by the ability of high-density lipoproteins to promote cholesterol efflux from endothelial cells (ECs). The ATP-binding cassette transporters A1 and G1 (ABCA1 and ABCG1) interact with high-density lipoproteins to promote cholesterol efflux from ECs. To determine the impact of endothelial cholesterol efflux pathways on atherogenesis, we prepared mice with endothelium-specific knockout of Abca1 and Abcg1 . Approach and Results—: Generation of mice with EC-ABCA1 and ABCG1 deficiency required crossbreeding Abca1 fl/fl Abcg1 fl/fl Ldlr −/− mice with the Tie2Cre strain, followed by irradiation and transplantation of Abca1 fl/fl Abcg1 fl/fl bone marrow to abrogate the effects of macrophage ABCA1 and ABCG1 deficiency induced by Tie2Cre. After 20 to 22 weeks of Western-type diet, both single EC- Abca1 and Abcg1 deficiency increased atherosclerosis in the aortic root and whole aorta. Combined EC- Abca1/g1 deficiency caused a significant further increase in lesion area at both sites. EC- Abca1/g1 deficiency dramatically enhanced macrophage lipid accumulation in the branches of the aorta that are exposed to disturbed blood flow, decreased aortic endothelial NO synthase activity, and increased monocyte infiltration into the atherosclerotic plaque. Abca1/g1 deficiency enhanced lipopolysaccharide-induced inflammatory gene expression in mouse aortic ECs, which was recapitulated by ABCG1 deficiency in human aortic ECs. Conclusions—: These studies provide direct evidence that endothelial cholesterol efflux pathways mediated by ABCA1 and ABCG1 are nonredundant and atheroprotective, reflecting preservation of endothelial NO synthase activity and suppression of endothelial inflammation, especially in regions of disturbed arterial blood flow. Abstract : Supplemental Digital Content is available in the text.